(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study examines the impact of female board participation on earnings management in Nigerian manufacturing firms between 2014 and 2024. Drawing from annual reports of sixteen listed companies, female CEO power and female board size were used as measures of board gender participation, while earnings variability served as a proxy for earnings management. Employing a static panel regression under an ex-post facto research design, the results indicate that female CEO power has a negative but statistically insignificant association with earnings management, whereas female board size shows a positive and marginally significant effect at the 10% level. These findings suggest that while the presence of women in top leadership positions may not independently deter earnings manipulation, larger female representation on boards could be linked to increased earnings management activities, potentially reflecting contextual and governance factors in the Nigerian corporate environment. The study recommends appointing more qualified women as CEOs, enhancing their ownership stakes to strengthen influence, and ensuring that female board members are empowered to contribute effectively. These insights contribute to corporate governance debates and offer guidance for policy reforms aimed at improving board diversity and financial reporting integrity.